Subordination of women and patriarchal gender relations at Islamic poor community - Ahmad Ridwan; Emy Susanti (Masyarakat, Kebudayaan dan Politik, 2019)
This study focuses on poor women in the social environment (village) in the center of the Surabaya metropolis with classical Islamic culture and rules. Social relations and “pesantren culture” are felt in this place. For example: women must wear headscarves every day, men use koko sarongs and shirts, reading the holy verses of the Qur’an are a daily habit. In fact, elementary school children have become memorizers of the Qur’an (hafidz). This place produces “kyai” and “nyai” (saints in Javanese Islam). This study focuses on unequal gender relations between men and women so that poor women experience subordination, as well as empowerment of poor women in the Islamic community in the middle of big cities. Women, especially poor women, have very low bargaining power because of the patriarchal culture and Islamic rules there. Even though poor women help to make a living for the family, all important decisions remain with the husband (male). The methodology used is qualitative. Conduct in-depth interviews with poor women who were married in that place. Researchers also make observations about their daily activities in the community. The result, using Michel Foucault’s power relations theory analysis, found that poor women get unfair relationships every day. They always lose with their husbands in any case. They are always oppressed and subordinated. Poor women get a discourse that women are the second social class in this life. They are a male partner, not the first person. So, important decision makers in the family are always men, not women. Although women help their husbands to work outside the home, decision makers are always husbands. Poor women are also powerless in government development programs. Even though the relationship is not equal, all women accept it because it comes from God’s destiny (Allah SWT). This phenomenon is real and occurs in the center of a big city (Surabaya) which is one of the largest cities in Indonesia.